Asphalt concrete reconstruction and computational mechanical modelling using 3D grid division (2020)
This study introduces a three-dimensional (3D) grid division approach to account for the internal composition of asphalt concrete (AC) when performing finite element (FE) computational mechanics simulations. This methodology, which is extension of an existing two-dimensional (2D) technique, initiates by processing Computed Tomography (CT) scan data, to create a simplified reconstruction of an asphalt concrete (AC) specimen. Once the sample has been reconstructed, it is divided into two main phases: i) the coarse aggregate, and ii) the asphalt mortar. Then, the specimen is partitioned in homogenized cubic cells to approximate the mechanical response of the sample. In this study, 70 consecutive images were used to reconstruct a 70x70x70 mm AC sample. A grid was used to divide the sample into cubic cells and approximate the aggregate fraction within the cell. Using two binary interpolation rules (50/50 and 75/25), each cell was assigned a phase: either aggregate or asphalt mortar, depending on the limit value of each rule. This procedure was done for 10 different partitions; (2, 4, 6, 8, 10, 15, 20, 25, 30, 40); the number of cells corresponded to the number of partitions cubed, so there was a maximum of 64,000 cells, each 2.8x2.8x2.8 mm in size. To estimate a mechanical response from the simplified reconstructed specimen, the AC model was then subjected to a constant displacement using the FE software Abaqus®. It was found that the 50/50 rule converges with 8 divisions, and the overall stress reported in the specimen tends to decrease as the number of divisions increase. For the 75/25 rule, the opposite was found, as the number of divisions increase the recorded overall stress increased; also, the results for this rule did not converge and the end measured stress where one order of magnitude smaller than those of the 50/50 rule